A Comparison of Onset of Anesthesia Between Spinal Bupivacaine 5 mg with Immediate Epidural 2% Lignocaine 5ml and Bupivacaine 10 mg for Caesarean Delivery - H.L. Baby Rani; T. Haritha (Academia Anesthesiologica International, 2021)
Introduction: In separate surgeries, spinal anesthesia is usually performed using lidocaine percent 5 and bupivacaine percent 0.5. This procedure is followed by many difficulties, including extending the level of anesthetics to places greater than the local injection site. Materials and methods: This research was performed with 60 patients posted for elective caesarean delivery belonging to ASA Grade I & II. Patients were allocated randomly into 2 groups of 30 each. (Spinal bupivacaine 5 mg with instant epidural 2 percent lignocaine) mixed spinal epidural (CSE) group and Spinal (S) group (Spinal bupivacaine 10 mg). Results: Compared to patients who underwent mixed spinal-epidural anesthesia, patients in group S showed a quicker onset of anesthesia (meantime) (group CSE). There is no clinically relevant onset of anesthesia (p-value = 0.08). In group S, the time for the first hypotension is considerably early. For a value of < 0.001, the p-value is statistically important. In Category S, the lowest calculated SBP was substantially found. The p-value with a value of <0.001 is statistically important. In Group S, the number of patients with hypotension was slightly (p-value = 0.03) higher (19 patients) than in Group CSE (11 patients). Group CSE reported a statistically important early 2 segment regression period with a p < 0.001 value. The early recovery in the CSE community is statistically important, with a value of p<0.001. Conclusions: The low-dose CSE procedure, especially for high-risk patients at risk of precipitous hypotension, is a choice for supplying anesthesia for caesarean delivery.